2023
DOI: 10.3390/jcm12083024
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Related Differences among Adults with Hypertrophic Obstructive Cardiomyopathy Undergoing Transcoronary Ablation of Septal Hypertrophy

Abstract: (1) Background: The transcoronary ablation of septal hypertrophy (TASH) is an established therapy for hypertrophic obstructive cardiomyopathy (HOCM). Previous studies on this topic are characterised by a consistent male predominance and show a worse prognosis in females. (2) Methods: This study is a retrospective analysis of all TASH procedures conducted between 2006 and 2021 at a tertiary academic centre. A solution of 75 µm microspheres (Embozene®, Boston Scientific, Marlborough, MA, USA) was used as an embo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Furthermore, Alyaydin et al investigate the differences related to sex among adults with HCM who undergo alcohol septal ablation. They observed that women tend to present at a more advanced age and with more severe symptoms and that the procedure is safe and effective for both sexes, with advanced age at the time of the intervention as an independent predictor of mortality [ 33 ].…”
Section: Invasive Strategiesmentioning
confidence: 99%
“…Furthermore, Alyaydin et al investigate the differences related to sex among adults with HCM who undergo alcohol septal ablation. They observed that women tend to present at a more advanced age and with more severe symptoms and that the procedure is safe and effective for both sexes, with advanced age at the time of the intervention as an independent predictor of mortality [ 33 ].…”
Section: Invasive Strategiesmentioning
confidence: 99%